Fichte's Creuzer review and the transformation of the free will problem. (9th January 2018) - Martin, Wayne
Abstract: Fichte's early review of C. A. L. Creuzer's neglected and idiosyncratic skeptical book on free will posed a serious challenge to what at the time was emerging as a consensus Kantian position on the role of free choice ( Willkür ) in the generation of imputable action. Fichte's review was directed as much against Reinhold's important (and only recently published) letter on freedom of the will as it was against Creuzer himself. In the course of his brief review, Fichte suggests an important recasting of the strategy of the Kantian postulates of rational faith; he poses a dilemma for the Reinholdian understanding of the relationship among an autonomous practical will, a free power of choice, and the actions of natural human organisms; and he hints at a radical reappropriation of the rationalist doctrine of pre‐established harmony in re‐orienting the search for a defensible reconstruction of a broadly Kantian position on the problem of free will.